ANALISIS LOGAM BERAT TIMBAL (Pb) AND MANGAN (Mn) PADA AIR DARI TEMPAT PEMBUANGAN AKHIR (TPA) SAMPAH AIR DINGIN - Fatmi, Dini (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Final Disposal (TPA) of waste Air Dingin Padang City using open dumping system isexpected to negatively affect the groundwater and surrounding waterways. Research onthe content of heavy metals in landfill water flow in the Air Dingin were made in 2 (two)times that were before the rain and after the rain, then the results were compared with theapplicable standard. The content of heavy metals Pb and Mn in Final Disposal (TPA) ofwaste Air Dingin Padang City were 0,005-0,025 mg/L and 0,0-0,966mg/L. Pbconcentration exceeded the quality standard KEPMEN LH 51 in 1995 leachate pond,while the flow of water and monitoring wells Pb metal content exceeds the qualitystandards PP.RI.No.82 on 2001 and Mn outlet river exceeds the quality standardsPP.RI.No.82 on 2001. In population of all heavy metals well below the quality standardPP.RI.No.82 on 2001. The content heavy metals was affected by the distance of thelocation of waste, the pH value and after of the rain water around the landfill waste.Keyword : Final Disposal (TPA) of waste, heavy metals